Trend of fetal echocardiography use and comparison of medical costs for congenital heart disease treatment based on fetal echocardiography use in a Korean single center - Choi, Ho-Jung; Song, Mi-Kyoung; Lee, Sang-Yun; Kim, Gi-Beom; Bae, Eun-Jung; Park, Joong-Shin; Jun, Jong-Kwan; Kwon, Hye-Won; Lim, Hong-Gook; Kim, Woong-Han (Frontiers in Pediatrics, 2023)
Background: The rate of the prenatal diagnosis of congenital heart disease is increasing along with advances in fetal echocardiography techniques. Here, we aimed to investigate the trend of the use of fetal echocardiography over time and to compare the medical costs of congenital heart disease treatment according to whether fetal echocardiography was performed. Methods: We reviewed our hospital’s database, and patients who underwent the first surgery for congenital heart disease within 30 days of birth during 2005-2007, 2011-2013, and 2017-2019 were included. The severity of congenital heart disease diagnosed in each case was evaluated according to The Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery Congenital Heart Surgery Mortality Scores (STS-EACTS Mortality Scores) and Mortality Categories (STAT Mortality Categories). Results: In total, 375 patients were analyzed, and fetal echocardiography use increased significantly after the 2010s compared with in 2005-2007 (19.1% vs. 39%, p = 0.032 in Mortality Category 1-3; 15.5% vs. 69.5%, p = 0.000 in Mortality Category 4-5). Additionally, the mean STS-EACTS Mortality Score was higher in prenatally diagnosed patients than in postnatally diagnosed patients (2.287 vs. 1.787, p = 0.001). In the recent period, there was no significant difference in hospitalization durations and medical costs according to whether or not fetal echocardiography was performed. Conclusions: This single center study showed the use of fetal echocardiography is increasing. Further, prenatal diagnosis with fetal echocardiography causing no differences in medical costs in recent years. Therefore, we suggest that fetal echocardiography can be applied more widely without increasing the economic burden.